Functional outcome of patients treated with proximal humeral internal locking osteosynthesis plate in proximal humeral fractures - Jacob, Tigy Thomas; Nayak, Manmatha (International Journal of Research in Orthopaedics, 2020)
Background: Displaced or unstable proximal humeral fractures fare poorly with non-operative treatment. These are better treated with surgical intervention in order to prevent minimal displacement of tuberosity or articular surface from compromising the long term articular function. The objective was to assess the functional outcome of patients treated with PHILOS (the proximal humeral internal locking osteosynthesis) plate in proximal humerus fracture. Methods: 42 patients age group range between 20 and 80 years 61.9% are male and 38.1% are female treated with philos plate. Functional outcome measured by using Constant and Murley score. Results: 50% were Neer two part fractures, 35.7%, three part fractures, 14.3%, four part fractures. After 6 month follow up functional outcome assessed by using constant and Murley score. Excellent outcome in 1 (2.4%) good outcome in 13 (31%), fair outcome in 19 (45.2%) and poor outcome in 9 (21.4%) noted. Conclusions: PHILOS plate fixation of proximal humerus fracture is an effective surgical technique in maintaining stability of fractures and there is significant improvement in functional outcome.